Różnice dydaktyczne i edukacja. Rekonstrukcja przestrzeni narracyjnej w ujęciu Doroty Klus-Stańskiej (na przykładzie książki Paradygmaty dydaktyki. Myśleć teorią o praktyce) - Połonnikow , Aleksandr (Studia Edukacyjne, 2019)
The article is dedicated to the narrative space of D. Klus-Stańska’s book: Paradygmaty dydaktyki. Myśleć teorią o praktyce (Wydawnictwo Naukowe PWN, 2018). The research perspective adopted in it is oriented towards the analysis of difficulties encountered in the practice of the written scientific text, the aim of which is to present educational constructs of different quality and at the same time to facilitate students’ navigation within their multiplicity. The study also assesses the educational procedures of the author, who experiments with the organization of a scientific text addressed to students and its graphic design. In the course of analyses, the specificity of the author’s textual techniques was identified, involving e.g. contextualisation of the languages described and their linguistic deconstruction, as well as intertextual exposition of educational narratives.